Oxygen-Dependent Accumulation of Purine DNA Lesions in Cockayne Syndrome Cells - Marios G. Krokidis; Mariarosaria D’Errico; Barbara Pascucci; Eleonora Parlanti; Annalisa Masi; Carla Ferreri; Chryssostomos Chatgilialoglu (Cells, 2020)
Cockayne Syndrome (CS) is an autosomal recessive neurodegenerative premature aging disorder associated with defects in nucleotide excision repair (NER). Cells from CS patients, with mutations in CSA or CSB genes, present elevated levels of reactive oxygen species (ROS) and are defective in the repair of a variety of oxidatively generated DNA lesions. In this study, six purine lesions were ascertained in wild type (wt) CSA, defective CSA, wtCSB and defective CSB-transformed fibroblasts under different oxygen tensions (hyperoxic 21%, physioxic 5% and hypoxic 1%). In particular, the four 5′,8-cyclopurine (cPu) and the two 8-oxo-purine (8-oxo-Pu) lesions were accurately quantified by LC-MS/MS analysis using isotopomeric internal standards after an enzymatic digestion procedure. cPu levels were found comparable to 8-oxo-Pu in all cases (3–6 lesions/106 nucleotides), slightly increasing on going from hyperoxia to physioxia to hypoxia. Moreover, higher levels of four cPu were observed under hypoxia in both CSA and CSB-defective cells as compared to normal counterparts, along with a significant enhancement of 8-oxo-Pu. These findings revealed that exposure to different oxygen tensions induced oxidative DNA damage in CS cells, repairable by NER or base excision repair (BER) pathways. In NER-defective CS patients, these results support the hypothesis that the clinical neurological features might be connected to the accumulation of cPu. Moreover, the elimination of dysfunctional mitochondria in CS cells is associated with a reduction in the oxidative DNA damage.